Precision medicine in food allergy. Issue 5 (October 2018) - Arasi, Stefania; Mennini, Maurizio; Valluzzi, Rocco; Riccardi, Carla; Fiocchi, Alessandro
Abstract : Purpose of review: To familiarize the reader with the concept of precision medicine in food allergy through the most recent insights in the diagnosis, prognosis, and management of the disease. Recent findings: With the advent of omics sciences, a new era is commencing. Food protein allergens characterization and quantification together with the immunoglobulin E epitope mapping will contribute to the diagnosis/prognosis of food allergy and will lead to a better safety assessment of foods. The characterization of biomarkers able to identify specific phenotypes and endotypes will improve the diagnostic accuracy. This together with a better understanding of mechanisms of action of the different therapeutic options will allow the accurate selection of the appropriate patient. Summary: In the near future, advances in technologies and data interpretation will allow a better understanding of the pathogenesis of food allergy and the development of a personalized treatment tailored on the specific patient' profile.